Intracellular calcium release during in vitro mammalian embryonic development in the presence of Kalanchoe Pinnata extract / Nor Azila Md Ludin - Md Ludin, Nor Azila (2014)
Medium composition plays an important role in mammalian in vitro culture. The availability of commercial culture media with different formulations and chemical constituents indicates the specific need and application of using medium for in vitro culture. WM was selected in this study for rabbit and mouse embryo cultures. WM+1 mg/ml and WM+2.5 mg/ml of K. pinnata extract were used to investigate the efficacy of the extract on intracellular calcium release in relation to cleavage development of embryos. The embryos were cultured in the respective medium and the cleavage developments were observed daily for six consecutive days. The intracellular calcium release was measured from the 2- to 6/8-cell embryos and fluorescence imaging of nuclear materials, microtubules and mitochondria were obtained. Rabbit embryos cultured in WM, WM+1 mg/ml and WM+2.5 mg/ml of K. pinnata extract had developed to morula stage with 6.35 ± 6.32%, 4.44 ± 4.17% and 5.13 ± 2.92%, respectively. There was a significantly higher percentage of development at 3/4-cell stage (p<0.05) in WM+2.5 mg/ml of K. pinnata extract. The intracellular calcium release in 3/4-cell and 6/8-cell stages were in the range of 3.95-50.10 \xM and 24.50- 782.00 |iM, respectively. Embryos retrieved at 48 hours post hCG survived until blastocyst (0.84 ± 0.47%), 8-cell (2.01 ± 0.97%) and morula stage (2.20 ± 1.17%) in WM, WM+1 mg/ml and WM+2.5 mg/ml of K. pinnata extract, respectively. Low intracellular calcium release caused fragmented nuclei and the mitochondria and microtubules were aggregated only at the center part of blastomeres. The presence of K. pinnata extract as supplement for the culture medium had significantly enhanced the development of rabbit embryos at 3/4-cell stage and mouse embryos at 2-cell and 8-cell stage (p<0.05). Different formulations of herbal extract as supplement are required to improve the embryo development at each cell stage.